Impact of clipping dates and nitrogen application on yield and yield components of two six-rowed barley at two location of Sulaimani District - ahmad, maki mohammed; Mustafa, Kamil Mahmood; Muhammed, Sanarya Rafiq; Rashed, Almas Galal M. (Journal of Kerbala for Agricultural Sciences, 2018)
Abstract A field experiment was conducted under rainfed conduction of Bacrajo and Bazian locations (Iraq-Kurdustan region) during 2015-16 cropping season. The experiment consisted combinations of four cutting schedules (no clip, 80, 105, and 130 DAS), two barley varieties (Ibba-99 and Local variety) and two fertility levels (N 40 and 80 kg/ha-1). These 16 treatment combinations were evaluated under factorial randomized block design with three replications. Results revealed that application of no clip, Ibba-99 variety and N 80 kg ha-1 fertilizer as alone or in combinations significantly (P 0.05) increased almost all growth parameters, in most cases led to significant (P 0.05) increases number of spike m-2, number of grains spike-1, 1000 grain weight, HI, and gave the highest biological and grain yield at the two locations. Clipping systems, varieties and N levels as alone or in all possible combinations (two and three-way interaction) had significant (P 0.05) effects on grain yield. The highest grain yield for C0, Ibaa-99, N 80, C0 x Ibaa-99, C0 x N 80, Local var x N 80 and C0 x Ibaa-99 x N 80 were 4.351, 2.447, 2.509, 4.884, 4.782, 2.523 and 5.127 t ha-1, respectively at Bakrajo location, while at Bazyan location for C0, Ibaa-99, N 80, C0 x Local var, C0 x N 80, Local var x N 80 and C0 x Local var x N 80 were 5.311, 3.814, 5.817, 5.551, 3.895, 3.938 and 6.216 t ha-1, respectively. The best grain yield for dual purpose barley at three-way combinations with C1 x Local var x N 80 were 4.043 and 5.770 b t ha-1 at Bakrajo and Bazyan locations, respectively. For that, application of C0 x Ibaa-99 x N 80 and C0 x Local var x N 80 combinations at at Bakrajo and Bazyan locations, respectively may be the best option to achieve high grain in quantity, while C1 x Local var x N 80 at the two locations for dual purpose barley may be the best option to achieve acceptable grain and forage in quantity under guaranteed rainfed Iraq-Kurdustan region.